Arachnoid Cysts in Athletes with Sports-Related Concussion: A Case Series and Literature Review - Andrew R. Stevens; Kamal M. Yakoub; David J. Davies; Antonio Belli; Philip J. O'Halloran (SpringerOpen, 2024)
Abstract Background Arachnoid cysts (AC) are associated with a risk of rupture or haemorrhage following head impact and pose a potential predisposing factor for significant complications of sport-related concussion. Despite a recognised association between ACs and intracranial haemorrhage/cyst rupture, the risk profile of participating in contact sports with AC is not well defined. We report a retrospective case series of players presenting to the Birmingham Sports Concussion Clinic between 2017 and 2023 and underwent MRI head, with a comprehensive review of the prior literature. Results 432 athletes underwent MRI of which 11 were identified to have AC (middle fossa n = 8; posterior fossa n = 2, intraventricular n = 1). Average maximal diameter was 4.1 ± 1.2 cm. 64% had a protracted recovery (≥ 3 months). 9% experienced an AC specific complication (cyst rupture, complete neurological recovery, maximal diameter 6.5 cm, Galassi II, 4 previous concussions). 91% of patients (mean maximal diameter 3.9 ± 1.0 cm) experienced no complications despite multiple previous accumulated sports-related concussions (mean 3.3, range 1-9). Case studies from the literature are summarised (n = 63), with 98% reporting complications, none of which resulted in adverse or unfavourable neurological outcomes. Across prospective and retrospective cohort studies, 1.5% had a structural injury, and (where outcome was reported) all had a favourable outcome. Conclusions AC is an incidental finding in athletes, with the majority in our cohort having sustained serial concussions without AC complication. The single complication within this cohort occurred in the largest AC, and AC size is proposed as a tentative factor associated with increased risk of contact sports participation. Complications of AC appear to be a rare occurrence. This case series and review has not identified evidence to suggest that participation in sports with AC is of significant risk, though individualised assessment and discussion of the potential risks of contact sports participation should be offered.